Respon Galur Leuconostoc mesenteroides dan Weissella confusa terhadap pH Kondisi Pertumbuhan Menggunakan Antibiotik sebagai Indikator - AMARILA MALIK; DEWI PUSPITA; RIZKI AYU AMALIA (Fakultas Farmasi Universitas Pancasila, 2013)
Lactic acid bacteria is known to contribute to human health as exopolysaccharide producer, bacteriocin producer, live vaccins, starter in fermentation process and as probiotics. This study aimed to observe Leuconostoc mesenteroides and Weisella confusa strains response under manipulated growth condition for carbon source composition and on pH as a model, using various antibiotics as indicator. MRS and modified MRS (50% normal dextrose concentration) were used. Modification of pH representing acidic and alkaline condition were 4.6 and 9.0. Disc diffusion method was employed using six different antibiotics. Result showed that all strains grown in acidic standard MRS tend to be more sensitive to amoxicillin (Am), chloramphenicol (Ch) and polymyxin B (PoB), but more resistant to ciprofloxacin (Ci), while in the acidic modified MRS, the strains respond more sensitive to Am, Ch, Ci and PoB. When grown in alkaline standard MRS, all strains respond more sensitive to Am, Ci and PoB, but more resistant to Ch, while in alkaline modified MRS, they respond more resistant to Am and Ch but more sensitive to Ci and PoB. Most of the strains did not show inhibition against vancomycin and none of strains showed inhibition against sulphamethoxazole-trimethoprim under conditions applied.